2013
DOI: 10.1016/j.mambio.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Rumination of different-sized particles in muskoxen (Ovibos moschatus) and moose (Alces alces) on grass and browse diets, and implications for rumination in different ruminant feeding types

Abstract: The obligatory, periodic regurgitation of forestomach material and its subsequent re-mastication is the hallmark of the most diverse extant large herbivore group, the ruminants. Although the process of rumination is well understood in domestic species, differences between free-ranging wild ruminant species, for example of different body size or different feeding type, remain speculative to date. Here we investigate the proportion of plastic particles of varying size (1, 10 and 20mm) and density (1.03, 1.20 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 99 publications
2
24
1
Order By: Relevance
“…The results of this study corroborate known differences in the selective retention of digesta particles in ruminants that lead to different‐sized faecal particles: large particles are rare in ruminant faeces and represent digesta fractions that escape the forestomach comparatively soon after ingestion; most particles are retained and submitted to repeated comminution via rumination (Lauper et al., ; Udén, ). Differences in MRT between large and small particles in the ruminant species were not only significant, but also of a magnitude (8–9 hr) that is relevant in terms of fermentative digestion (Hummel, Südekum, Streich, & Clauss, ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results of this study corroborate known differences in the selective retention of digesta particles in ruminants that lead to different‐sized faecal particles: large particles are rare in ruminant faeces and represent digesta fractions that escape the forestomach comparatively soon after ingestion; most particles are retained and submitted to repeated comminution via rumination (Lauper et al., ; Udén, ). Differences in MRT between large and small particles in the ruminant species were not only significant, but also of a magnitude (8–9 hr) that is relevant in terms of fermentative digestion (Hummel, Südekum, Streich, & Clauss, ).…”
Section: Discussionsupporting
confidence: 83%
“…Note the general similarity to Figure 2, and the inverse pattern in particle sizes in the ruminant. This is because particle sizes do not denote different ingested markers in this experiment, but different fractions of the same marker escaping the forestomach; in ruminants, the minor fraction of large particles that escapes rumination is typically excreted very soon after ingestion represent digesta fractions that escape the forestomach comparatively soon after ingestion; most particles are retained and submitted to repeated comminution via rumination (Lauper et al, 2013;Udén, 1978). Differences in MRT between large and small particles in the ruminant species were not only significant, but also of a magnitude (8-9 hr) that is relevant in terms of fermentative digestion (Hummel, Südekum, Streich, & Clauss, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this argument, Hooper and Welch () found that legumes change specific gravity faster than grasses. Larger particles that support a floating fibre mat for longer could be the reason why grass diets, irrespective of the forestomach physiology of the ruminant, trigger a more pronounced ‘filter bed effect’ where small particles are retained in the rumen due to entrapment in the mat (Clauss et al., ; Lauper et al., ). Hence, physiological adaptations in ‘cattle‐type’ ruminants to increase fluid flow through the rumen (Dittmann et al., ; Hummel et al., ) that also lead to a higher availability of low‐viscosity fluid in this organ, and physicochemical properties of grass itself, combine to result in the observed difference in rumen contents stratification between browsing and grazing ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Based on those early observations, a theory was developed that linked the throughput of great amounts of a low-viscosity fluid in cattle-type ruminants to adaptations whose ultimate objective was considered to be the enhancement of the natural tendency of grass forage to stratify in the rumen, thus facilitating a more efficient selective particle retention, size reduction via rumination, and hence digestibility (Clauss et al, 2003;Clauss et al, 2008b). When this theory was tested experimentally, however, results indicated that the particle retention and sorting mechanism did not differ fundamentally between a moose-type and a cattle-type species, even though differences in rumen content stratification, rumen fluid viscosity, and the relative rumen fluid throughput could be demonstrated (Lechner et al, 2010;Clauss et al, 2011;Lauper et al, 2013).…”
Section: Explanatory Approach Iiia: Maximizing Stratification?mentioning
confidence: 99%